The whites of their eyes - Clements, Andrew, 1949-2019.; Stower, Adam (New York : Atheneum Books for Young Readers, 2012)
With a key to the Oakes School in his possession Benjamin, his friend Jill, and a new friend continue to seek ways to protect the school and their town but Lyman, the janitor and a spy, has new tricks up his sleeve.
Ages 7-10.
Keywords: Schools -- Juvenile fiction; Spy stories; Sailing -- Juvenile fiction; Mystery and detective stories; Schools -- Fiction; Spies -- Fiction; Sailing -- Fiction